Successful prolonged intermittent renal replacement therapy in managing isolated coronary artery bypass graft surgery-associated acute kidney injury: A case report - Huzaiby, Adam; Wardoyo, Suprayitno (Indonesian Vascular Access Association (IVAA), 2024)
Introduction: Unstable angina pectoris is one of the most underappreciated conditions by emergency department doctors. Unfortunately, the UAP is a type of heart attack that is usually caused by the deadliest type of CAD, namely the left main disease and three-vessel diseases. Both types are excellent candidates for operative revascularization with a satisfying result. Not infrequently, the acute renal complications after CABG surgery often become catastrophic. This study aims to evaluate our experiences in managing our patients with AKI following a conventional CABG surgery as a postoperative complication. Case description: A 69-year-old man was admitted to the ward to undergo a scheduled elective CABG surgery on the following day. The patient has a history of UAP, and a CAG study that was done three weeks earlier indicated that the culprit was a left main disease. The LIMA was anastomosed to the distal segment of the LAD, and one graft of GSV was anastomosed to the OM. Following the surgery, the patient experiences an unstable rapid response of AF and stage three AKI. Eventually, the patient must undergo two times of SLEDDs. After a second dialysis, the patient’s serum creatinine was lowered and the stage of the AKI was downgraded. After close monitoring for fifteen days, the patient’s serum creatinine gradually became normal. The dialysis access is removed, and the patient does not need a subsequent routine dialysis following discharge from our hospital. Conclusion: The incidence of AKI following CABG surgery can be multifactorial. An alternative technique instead of using a CPB machine, judicious use of blood products, and prevention and treatments of a POAF should be considered. The PIRRT can be chosen as an alternative modality to CRRT with the same outcome quality for managing stage three AKI following CABG surgery.